El Balance Social como instrumento de medición de la Responsabilidad Social en la COAC Fernando Daquilema Ltda., periodo 2022 - Amanta Pilco, Erica Paulina (2024)
ABSTRACT: Social Responsibility has become a fundamental pillar in managing organizations committed to their environment and their impact on society. In this context, the Social Balance emerges as a comprehensive and revealing tool that allows evaluating the commitment and contribution of an entity toward social well-being. The present investigative work entitled "The Social Balance as an Instrument for Measuring Social Responsibility in the COAC Fernando Daquilema Ltda., Period 2022" was developed to evaluate the Social Balance as an instrument for measuring social responsibility in said entity. The methodological process is composed of the deductive method for which financial and statistical information of the Cooperative was collected. Likewise, the survey was used as a data collection technique, which was directed to the heads of the main departments that contributed information for the preparation of the Social Balance. It was concluded that the Social Balance is a valuable instrument to measure Social Responsibility in the COAC Fernando Daquilema Ltda., since its application provided a comprehensive vision of the actions and impact of the cooperative on society, evidencing that the entity respected ethical standards. The information about its social activities was communicated clearly and truthfully, showing its commitment to Social Responsibility and evidencing areas of strength and opportunity for improvement.